Safety and feasibility assessment of extending the flushing interval in totally implantable venous access port flushing during the non-treatment stage for patients with breast cancer - Wang, Yinhuan; Tian, Hao; Chen, Xianchun; Zhang, Jiasi; Wang, Li; Fan, Haiyan; Zhang, Yi; Qi, Xiaowei; Hu, Shaoyi; Yang, Ying (Frontiers in Oncology, 2022)
Aim: To investigate the safety and feasibility of extending the flushing interval for the totally implantable venous access port (TIVAP) during the non-treatment stage in patients with breast cancer (BC) by retrospectively analyzing the patients’ clinical data, including the incidence of TIVAP-related complications. Methods: This single-center retrospective study included patients with BC who underwent TIVAP implantation at our hospital between January 2018 and March 2021 during their non-treatment phase and visited the hospital regularly for TIVAP flushing. Among the 1013 patients with BC who received TIVAP implantation, 617 patients were finally included on the basis of the inclusion and exclusion criteria and divided into three groups according to the length of the flushing interval: group 1 (≤30 days, n = 79), group 2 (31–90 days, n = 66), and group 3 (91–120 days, n = 472). The basic characteristics of patients in each group and the incidence of TIVAP-related complications (catheter obstruction, infection, and thrombosis) were analyzed. Results: No significant intergroup differences were observed in age, body mass index (BMI), tumor stage, pathological staging, implantation approach, chemotherapy regimen, duration of treatment, and TIVAP-related blood return rate (P > 0.05). Among patients from all three groups, 11 cases of catheter pump-back without blood and eight cases of TIVAP-related complications such as infection, thrombosis, and catheter obstruction were recorded. However, no significant differences in TIVAP-related complications were observed among the three groups (P > 0.05). Conclusion: Extending the TIVAP flushing interval beyond three months during the non-treatment stage in BC patients is safe and feasible and did not increase the incidence of TIVAP-related complications.